Historical structure and composition of ponderosa pine and mixed-conifer forests in south-central Oregon - Hagmann, R. Keala; Franklin, Jerry F.; Johnson, K. Norman (Forest ecology and management, 2013)
•Reference conditions based upon a timber inventory conducted from 1914 to 1922.•Large ponderosa pine dominated basal area on pine and mixed-conifer sites.•Forests were predominantly low density at less than a third of current density.•Fire regime influenced structure and composition more than site productivity. We summarized structure and composition of dry forests from a 90-year-old timber inventory collected by the Bureau of Indian Affairs on the former Klamath Indian Reservation (now part of the Fremont-Winema National Forest). This analysis includes data from 424,626 conifers ⩾15cmdbh on 3068 transects covering 6646ha. The data represent a 10–20% sample of 38,651ha of forest growing on sites that are classified as ponderosa pine (Pinus ponderosa) and mixed-conifer habitat types distributed within the 117,672 ha of the study area. Large, drought- and fire-tolerant ponderosa pine dominated these forests. Large tree (>53cmdbh) basal area (13±7m2/ha) contributed 83±16% of total basal area; 81±20% of the large-tree basal area was ponderosa pine. Composition and structure of forests on mixed-conifer sites were very similar to those on ponderosa pine sites. Variability in composition and structure was recorded on all habitat types and was highest on moist mixed-conifer sites. Stand densities (trees per hectare, tph) have more than tripled over the past 90years from 68±28tph to a current density of 234±122tph recorded in Current Vegetation Survey data collected by the United States Forest Service. Mean basal area, however, increased by less than 20%. Basal area of large trees (>53cmdbh) has declined by >50%, and the abundance of large trees as a proportion of the total number of trees per hectare has decreased by more than a factor of five. This landscape-level record of historical forest conditions allows inferences about structure and composition across tens of thousands of hectares. A historical landscape emerges which supports current working hypotheses that frequent, low- to moderate-severity wildfires maintained a predominantly low-density forest dominated by large, fire- and drought-tolerant ponderosa pines across a significant moisture and productivity gradient from the driest ponderosa pine to the mixed-conifer habitat types.